Les ressources de territoires et les territoires de ressources - Georges Benko; Bernard Pecqueur (Finisterra - Revista Portuguesa de Geografia, 2001)
economical geography has known a revival since the 1990s; we even speak of a «new economic geography». Globalisation, metropolisation, the formation of free-trade zones, international exchanges, the linking of the global with the local are all themes at the centre of the concern about spatial economy. But globalisation does not necessarily mean homogenisation of the spaces. The notion of territory reappears in economical analyses because territories offer the market resources that are specific, untransferable and incomparable. These specific resources render the areas diversified and stabilize the emplacement of economic activities. In the next few years, one of the main subjects of research in economic analysis will probably be the study of the process of revealing and eveloping new resources that emerge from the uniqueness of the areas and human groups in a context where information logic controls the service economy.